Pengaruh Intensitas Aset Tetap, Beban Pajak Tangguhan Dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak: Studi Empiris Pada Perusahaan Consumer Non-Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Sariningsih, Neneng; Enan Trivansyah (UNPERBA, 2024)
This study aims to prove empirically regarding the effect of fixed asset intensity, deferred tax expense and sales growth on tax avoidance. The population of this study is consumer non-cyclicals companies listed on the Indonesia Stock Exchange for 2017-2021. The sampling technique in this study was purposive sampling. So that the sample used was 36 companies with 5 years of observation. The research method used is a quantitative method using secondary data. The analysis technique used is panel data regression analysis with the Eviews 9 program by analyzing descriptive statistics, panel data regression model test, panel data regression model estimation, classical assumption test, panel data regression analysis, coefficient of determination, T statistical test and F statistical test. The results of this study indicate that partial fixed asset intensity has a significant effect on tax avoidance, partially deferred tax expense has no effect on tax avoidance, partially sales growth has a significant effect on tax avoidance. Simultaneously the intensity of fixed assets, deferred tax expense and sales growth affect tax avoidance.